Le management fantôme de la médecine - Sismondo, Sergio (ENS Éditions, 2023)
While most actors in the drug production chain should operate under the label of science, their knowledge is in fact drawn from streams of knowledge that have been fed, spread and maintained by the pharmaceutical industry, in an intimate dialogue between science and marketing. Operating in the shadows, many “invisible hands” working for Big Pharma elaborate this knowledge: publication planners commission ghostwritten medical journal articles; key opinion leaders and sales representatives are recruited and deployed to subtly change doctors’ behaviour; patient organisations, influenced by the industry, spread biased points of view on diseases and treatments. Ultimately, at the end of this ghostly production chain driven by this “assemblage marketing”, prescriptions written by doctors will “naturally” make way for the new drugs promoted by pharmaceutical companies. Addressing a wide audience, Sergio Sismondo’s aim, with this book of which we offer here a previously unpublished translation, is to lift the veil on the ghost management in the pharmaceutical industry, a management we should all be concerned about, given its major impact on public health.